2018 5th International Conference on Coastal and Ocean Engineering (ICCOE 2018). (July 2018) - Unknown
Abstract : PREFACE It is my great pleasure to welcome you to the 2018 5th International Conference on Coastal and Ocean Engineering (ICCOE 2018) which was held in Shanghai, China during 27-29 April, 2018. ICCOE 2018 was dedicated to issues related to Coastal and Ocean Engineering. I, Prof. Hu Yihuai, from Shanghai Maritime University, China, held the keynote speech with title "Research into Sail-Assisting Technology for Ocean-Going Ships". Prof. CHOU Loke Ming from Tropical Marine Science Institute, National University of Singapore, Singapore had a keynote speech with title "Biodiversity Enhancement of the Urbanized Coastal Environment". Prof. Gordon Huang from Faculty of Engineering and Applied Science, University of Regina, Canada had a keynote speech with title "Factorial-Based Ecological Input-Output Model to Support Industrial Policy Formulation". Prof. Koh Hock Lye from Sunway University, Malaysia, held a keynote speech with title "The Life We Want: Achieving United Nation Sustainable Development Goals 2030".